Changing values and beliefs in 85 countries : trends from the values surveys from 1981 to 2004 - Halman, Loek. (European Values Studies, 2008)
This book presents the trends in beliefs and values of people in 85 countries around the world from 1981 to 2004. Based on survey data collected in 1981-1984 and 1989-1993 by the European Values Study, the 1995-1997 World Values Surveys and the 1999-2004 European Values Study and World Values Surveys, it examines trends in human values concerning economics, politics, religion, family, gender roles, civic engagement and ethical concerns and important contemporary issues such as the environment, technology, identity, life satisfaction and human happiness. It is a valuable tool for understanding the cultural patterns of countries and how human values are changing. It will be useful to social scientists, journalists, business executives, politicians and policy-makers working in an increasingly globalized world.